2018
DOI: 10.1177/1054773817751527
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health–Ill Health Differences in Disease Severity and Its Sociodemographic Biobehavioral Predictors Among Patients With Knee Osteoarthritis

Abstract: Our aim in this cross-sectional study was to investigate mental health-ill health differences in disease severity and its sociodemographic biobehavioral predictors among patients with knee osteoarthritis (OA). Applying convenient sampling, 180 patients with knee OA in Tabriz, Iran, were recruited to participate in completing a three-section questionnaire (SF-12, Lequesne Algofunctional Index and Self-Management Behaviors Scale). Separate hierarchical multiple linear regressions were performed with OA severity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 36 publications
(42 reference statements)
0
9
0
Order By: Relevance
“…In addition, 3 studies reported Lequesne Algofunctional Index of Disease Severity mean scores in patients with symptomatic/radiographic knee OA ( Table 4 ). 19 , 21 , 30 Among the population in Tunisia, Hana et al reported a mean severity score of 11, indicating very severe disability, and scores significantly higher in those ≥65 years of age compared with those <65 years of age. 21 In a Cameroon study, Bija et al found that the proportion of patients within higher score ranges increased with severity of radiographic grade of knee OA and 40% of patients with grade 4 symptomatic/radiographic knee OA had a score indicating extremely severe disability.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, 3 studies reported Lequesne Algofunctional Index of Disease Severity mean scores in patients with symptomatic/radiographic knee OA ( Table 4 ). 19 , 21 , 30 Among the population in Tunisia, Hana et al reported a mean severity score of 11, indicating very severe disability, and scores significantly higher in those ≥65 years of age compared with those <65 years of age. 21 In a Cameroon study, Bija et al found that the proportion of patients within higher score ranges increased with severity of radiographic grade of knee OA and 40% of patients with grade 4 symptomatic/radiographic knee OA had a score indicating extremely severe disability.…”
Section: Resultsmentioning
confidence: 99%
“…Comparisons with the other studies could not be made, however, because a different scoring scale was used. 30 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 1 , 11 , 12 Previous observational studies have already established the association between social isolation and osteoarthritis. 14 , 27 However, the traditional observational study designs are susceptible to interference from reverse causality and confounding factors, which limits the understanding of the relationship between social isolation and osteoarthritis. More importantly, different from general physical risk factors, the causal relationships between mental determinants and physical conditions are usually more complicated, which could be bidirectional.…”
Section: Discussionmentioning
confidence: 99%